Corrigendum to “B-mode ultrasonography and ecobiometric parameters for assessment of embryonic and fetal development in sheep” [Anim. Reprod. Sci. 197 (2018) 193–202] (Animal Reproduction Science (2018) 197 (193–202), (S0378432018304895), (10.1016/j.anireprosci.2018.08.028)) - Correia Santos, Victor José [UNESP]; Kako Rodriguez, Mariana Garcia [UNESP]; del Aguila da Silva, Priscila [UNESP]; Gomes Mariano, Renata Sitta [UNESP]; Taira, Augusto Ryonosuke [UNESP]; de Almeida, Vivian Tavares [UNESP]; Ramirez Uscategui, Ricardo Andrés [UNESP]; Nociti, Ricardo Perecin [UNESP]; Maia Teixeira, Pedro Paulo; Rossi Feliciano, Marcus Antonio [UNESP]; Russiano Vicente, Wilter Ricardo [UNESP] (Elsevier, 2020)
The authors regret to inform that the protocol number of two scholarships were missing. The acknowledgements section must be changed to: Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP) for scholarship (2014/15422-0), (2017/14957-6), (2019/15182-8) and Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES) provided scholarship funds. The authors would like to apologise for any inconvenience caused.